Adenovirus‐mediated artificial microRNA against human fibrinogen like protein 2 inhibits hepatocellular carcinoma growth. (5th July 2016) - Wang, Ming; Liu, Junhui; Xi, Dong; Luo, Xiaoping; Ning, Qin
Abstract: Background: Human fibrinogen‐like protein 2 (hFGL2) is overexpressed in various human solid tumors and is associated with tumor growth, invasion and angiogenesis of hepatocellular carcinoma (HCC) LM6 cells. In the present study, an adenoviral vector expressing an artificial microRNA (miRNA) against hfgl2 (Ad‐hfgl2‐miRNA) was used to evaluate the effect of FGL2 knockdown on cell proliferation and tumor growth of HCCLM6 xenografts. Methods: Ad‐hfgl2‐miRNA was constructed and its effect on hFGL2 expression and cell proliferation was analyzed. The xenograft tumor model was established in nude mice and this was accompanied by intratumoral injection of Ad‐hfgl2‐miRNA when the tumor volume had reached 100 mm 3 . The volume of the tumor xenograft was recorded and angiogenesis in the tumor xenograft was assessed. Results: Ad‐hfgl2‐miRNA significantly downregulated hFGL2 expression at both the mRNA and protein levels and exerted an inhibitory effect on proliferation in HCCLM6 cells. In HCCLM6 tumor‐bearing mice, the tumor volume significantly decreased following the intratumoral injection of Ad‐hfgl2‐miRNA compared to that of control groups. Additionally, Ad‐hfgl2‐miRNA also exhibited potent anti‐angiogenic effects. Conclusions: HFGL2 might be a potential target for controlling angiogenesis in HCC and hfgl2 gene silencing via miRNA may be an alternative strategy for the management of HCC. Copyright © 2016 John Wiley & Sons, Ltd.